The incredible story of how Jair Bolsonaro prevented a war: memetics and dialectical image: memetics and dialectical image (Intercom - Brazilian Journal of Communication Sciences, 2026)
In February 2022, at the height of tensions between Russia and Ukraine, former president Jair Bolsonaro traveled to Moscow to hold official meetings. Immediately, his supporters began to speculate about a secret motivation for the trip: to avoid the conflict between the two nations. In the days that followed, a flood of memes on different platforms characterized Bolsonaro as a promoter of world peace, while others mocked such claims. The aim of this paper is to analyze this "memetic war" as representative of the power that memes have been exerting on the Brazilian (and global) political scene. Taking as theoretical tools the notion of “dialectical image” and the structural relations that memes entertain with religious experience, I propose that public discourse has been strongly conditioned by a "memetic logic" that spreads virally through the social fabric in the current conditions of cyberculture.
Keywords: war; memes; imaginary; dialectical image